Resting-state electroencephalography changes in poststroke patients with visuospatial neglect - Zhang, Yichen; Ye, Linlin; Cao, Lei; Song, Weiqun (Frontiers in Neuroscience, 2022)
Background: This study aimed to explore the electrophysiological characteristics of resting-state electroencephalography (rsEEG) in patients with visuospatial neglect (VSN) after stroke. Methods: A total of 44 first-event sub-acute strokes after right hemisphere damage (26 with VSN and 18 without VSN) were included. Besides, 18 age-matched healthy participants were used as healthy controls. The resting-state EEG of 64 electrodes was recorded to obtain the power of the spectral density of different frequency bands. The global delta/alpha ratio (DAR), DAR over the affected hemispheres (DARAH), DAR over the unaffected hemispheres (DARUH), and the pairwise-derived brain symmetry index (pdBSI) (global and four bands) were compared between groups and receiver operating characteristic (ROC) curve analysis was conducted. The Barthel index (BI), Fugl-Meyer motor function assessment (FMA), and Berg balance scale (BBS) were used to assess the functional state of patients. Unilateral neglect was assessed using a battery of standardized tests. Results: We found that patients with VSN performed poorly compared with those without VSN. Analysis of rsEEG revealed increased delta and theta power and decreased alpha and beta power in stroke patients with VSN. Compared to healthy controls and poststroke non-VSN patients, patients with VSN showed a higher DAR (P < 0.001), which was significantly positively correlated with the BBS (DAR: r = -0.522, P = 0.006; DARAH: r = -0.521, P = 0.006; DARUH: r = -0.494, P = 0.01). The line bisection task was positively correlated with DAR (r = 0.458, P = 0.019) and DARAH (r = 0.483, P = 0.012), while the star cancellation task was only positively correlated with DARAH (r = 0.428, P = 0.029). DARAH had the best discriminating value between VSN and non-VSN, with an area under the curve (AUC) of 0.865. Patients with VSN showed decreased alpha power in the parietal and occipital areas of the right hemisphere. A higher parieto-occipital pdBSIalpha was associated with a worse line bisection task (r = 0.442, P = 0.024). Conclusion: rsEEG may be a useful tool for screening for stroke patients with visuospatial neglect, and DAR and parieto-occipital pdBSIalpha may be useful biomarkers for visuospatial neglect after stroke.